Student's Perception of Learning in the New Normal Era of Covid-19 - Wati, Dessy Riyana; Miranti, Mauren Gita; Suhartiningsih, Suhartiningsih; Purwidiani, Niken (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2022)
The Covid-19 pandemic forced learning to be adjusted to these conditions, the Ministry of Education and Culture has issued a circular letter Number 15 of 2020 regarding learning techniques in pandemic conditions or the new normal era which includes online and offline learning with a certain proportion. This study aims to determine the perception of SMK Tata Boga students towards learning in the new normal era which includes aspects of the learning experience, teaching skills in teaching, infrastructure, and the psychological condition of students when the learning process takes place. This research uses a descriptive quantitative method with a proportional stratified random sampling technique. The research population consisted of classes X, XI, and XII with a total of 179 students while the research sample was 64 students. The research instrument used a questionnaire with a Likert scale distributed via a google form link and to process research data using the TCR technique (respondent level of achievement). The overall research results calculated using the TCR technique got a score of 67.58% and were in good criteria, so it can be said that the new normal era learning carried out in one of the vocational schools went well. This research provides future benefits so that it becomes a consideration in building a system, a better curriculum. so it can be said that the learning of the new normal era carried out in one of the vocational schools went well. This research provides future benefits so that it becomes a consideration in building a system, a better curriculum.